HAK WARIS PEREMPUAN DALAM HUKUM ISLAM (KAJIAN KRITIS TERHADAP KESETARAAN GENDER) - Shalsadilla, Shavira; Subekti, Imam; Triyogo,; Akbar Ramadhan, Muhammad; Wahyudi, Sugeng; Mul Erowati, Eti (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This article discusses women's inheritance rights in Islamic law and gender equality in a modern context. The traditional inheritance division, allocating twice the share to males, is understood as balancing social responsibilities. However, with the evolving role of women in the family economy, a reevaluation of this rule is needed. The article examines contemporary scholars like Abdullah An-Naim, who advocate for reinterpretation of inheritance law through maqashid sharia. Inheritance law reforms in countries like Tunisia and Morocco, as well as Indonesia’s legal flexibility, are also discussed. The study recommends better legal education on women's inheritance rights and reforms for more equitable inheritance laws.